Constitution makers on constitution making : new cases - Ginsburg, Tom; Bisarya, Sumit (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Constitution-making is a major event in the life of a country, with constitutions often acting as a catalyst for social and political transformation. But what determines the visions, aspirations and compromises that go into a written constitution? In this unique volume, constitution makers from countries around the world come together to offer their insights. Using a collection of case studies from countries with recently written constitutions, Constitution Makers on Constitution Making provides a common framework to explain how constitutions are created. Scholars and practitioners very close to the process illuminate critical insights into how participants see constitutional options, how deadlocks are broken, and how changes are achieved. This vital volume also draws lessons concerning the role of courts in policing the process, on international involvement, and on public participation.
Introduction : Constitution makers on Constitution making / Tom Ginsburg and Sumit Bisarya -- Making and remaking Kenya's Constitutiong / Christina Murray -- Kosovo's Independence Constitution : a unilateral commitment to an internationalized pouvoir constituant / Gresa Caka Nimani -- Decisions deadlocks and deadlines in making South Africa's Constitution / Hassen Ebrahim -- Makers of our own history : upholding the revolution and unsettling coloniality in the drafting of Tunisia's 2014 Constitution / Mabrouka M'Barek -- Nepal's constitutional development and the challenges of Constitution making / Jeetendra Dev -- The constituent process in Ecuadorian process / Norman Wray with Jacob Hamburger -- Burundi : the search for constitutional peace / Didace Kiganahe.
Title from publisher's bibliographic system (viewed on 03 Nov 2022).
Keywords: Constitutional history; New democracies